Enriquecimiento sensorial aplicado a guacamayas en el zoológico de Santa Cruz por medio de estímulos olfativos enfocados en sus interacciones con su medio entre 2022 y 2023 (2022)
This report aims to present the experience obtained throughout the training practice carried out at the Santa Cruz Foundation zoo in which different tasks were developed that strengthen skills and important knowledge in the professional field. The project is developed by applying sensory enrichment techniques, not only in macaws, occupational and environmental enrichment was also carried out for several zoo species with satisfactory results, in addition to working as an assistant to the professional in charge where management of wild species was learned, including primates. , reptiles, birds, big cats, etc. being a profitable process that met the expectations of this experience